Feeding habits of the fishes Lutjanus peru and Lutjanus guttatus (Pisces: Lutjanidae) of Guerrero, México. - Rojas-Herrera, Agustín A (2004)
Diet composition of the Pacific snapper (Lutjanus peru) 130-684 mm fork length (FL) and the spotted snapper (Lutjanus guttatus) 120-550 mm FL, was analyzed. Monthly samples were obtained from commercial landings in three regions off the coast of Guerrero, Mexico. Percentage by number (%N), percentage by weight (%W), and percentage of occurrence (%O) were calculated for each prey and summarized as the index of relative importance. Both species are polyphagous predators feeding on a variety of prey: Sixty-eight prey items, mainly fish (%W = 50.9), crustaceans (%W = 35.6), and mollusks (%W = 7.2), were found in the stomach contents of L. peru, while 88 components were identified in the diet of L. guttatus, the most important prey being fish (%W = 50.8) and crustaceans (%W = 43.4). Diet overlap between species is not significant (p<0.05), indicating that competition for food is unlikely. Based on published values of the relative importance index, the diets of these Lutjanidae were analyzed considering different regions of the Pacific coast of Mexico and Costa Rica, and similarities among sites and species were discussed. The cluster analysis showed that similarities among species inhabiting in the same area are more important than within organisms of the same species living in different zones. Results suggest that prey availability rather than food selectivity, conditions the feeding behavior of these fish species.